1997
DOI: 10.1093/carcin/18.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide inhibits gap junctional intercellular communication in glutathione sufficient but not glutathione deficient cells

Abstract: Cell to cell communication via gap junctions is essential in the maintenance of the homeostatic balance of multicellular organisms. Aberrant intercellular gap junctional communication (GJIC) has been implicated in tumor promotion, neuropathy and teratogenesis. Oxidative stress has also been implicated in similar pathologies such as cancer. We report a potential link between oxidative stress and GJIC. Hydrogen peroxide, a known tumor promoter, inhibited GJIC in WB-F344 rat liver epithelial cells with an I50 val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
84
0
3

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(94 citation statements)
references
References 20 publications
7
84
0
3
Order By: Relevance
“…MK-801 antagonism of NMDA glutamate receptors (40) and inhibition of NOS have been shown to alter HBO 2 -induced seizure activity (25,60,70,227), and the actions of O 2 have been shown to decrease inhibitory (GABAergic) synaptic conductance (48). Gap junctional conductance through electrical synapses is also reduced by increased production of ROS (143,212), but the effects of HBO 2 on electrical coupling in mammalian neurons have not been investigated (56,98). This will be important to determine, however, because recent research has shown that CO 2 /H ϩ -chemosensitive neurons, which are coupled via gap junctions (56,57,98,190), are highly sensitive to HBO 2 and other chemical oxidants (152).…”
Section: Cellular Mechanism: O 2 -Induced Free Radicalsmentioning
confidence: 99%
“…MK-801 antagonism of NMDA glutamate receptors (40) and inhibition of NOS have been shown to alter HBO 2 -induced seizure activity (25,60,70,227), and the actions of O 2 have been shown to decrease inhibitory (GABAergic) synaptic conductance (48). Gap junctional conductance through electrical synapses is also reduced by increased production of ROS (143,212), but the effects of HBO 2 on electrical coupling in mammalian neurons have not been investigated (56,98). This will be important to determine, however, because recent research has shown that CO 2 /H ϩ -chemosensitive neurons, which are coupled via gap junctions (56,57,98,190), are highly sensitive to HBO 2 and other chemical oxidants (152).…”
Section: Cellular Mechanism: O 2 -Induced Free Radicalsmentioning
confidence: 99%
“…Some of the earliest evidence of oxidative stress in gap junction function are (a) oxidative-dependent hepatotoxic levels of carbon tetrachloride reversibly block GJIC between rat hepatocytes (81a); (b) antioxidants prevent tumor promoter-induced inhibition of GJIC in mouse hepatocytes (80a); (c) paraquat-generated ROS inhibit GJIC in mouse hepatocytes. More recently, we reported that hydrogen peroxide inhibited GJIC in a dose-dependent fashion (103 Glutathione (GSH) in its reduced form is the major reductant of H 2 O 2 in mammalian cells, and the depletion of this antioxidant commonly results in greater oxidative damage of macromolecules. This two-electron reduction of H 2 O 2 by GSH to H 2 O is catalyzed by glutathione peroxidase, and clearly serves as a protective role against peroxide-dependent oxidative injury.…”
Section: Oxidative Control Of Gap Junctionsmentioning
confidence: 99%
“…This two-electron reduction of H 2 O 2 by GSH to H 2 O is catalyzed by glutathione peroxidase, and clearly serves as a protective role against peroxide-dependent oxidative injury. A previous report determined the effect of depleting GSH on H 2 O 2 -dependent regulation of GJIC in a rat liver epithelial cell line (103). GSH depletion in this study was achieved by either the conjugation of GSH with diethylmaleate (DEM) or by inhibiting ␥-glutamylcysteine synthetase, which catalyzes the rate-limiting step of the biosynthesis of GSH, with buthionine sulfoximine (BSO).…”
Section: Oxidative Control Of Gap Junctionsmentioning
confidence: 99%
“…ROS have been associated with hormone stimulation (207,264) and specific gene activation (151,187,188) and can interact with signal transduction pathways (134, 223). Related to this point, glutathione has also been implicated in H 2 O 2 -mediated closure of gap junctions (129,273,308). H 2 O 2 -mediated closure of gap junctions also requires tyrosine kinase activity (126).…”
Section: Stressing Out the Neighborsmentioning
confidence: 99%
“…H 2 O 2 -mediated closure of gap junctions also requires tyrosine kinase activity (126). This was mediated by Cx43 hyperphosphorylation (127), was inhibited by glutathione depletion (273,308), and was not abrogated by free radical scavengers. Given these findings, it seems likely that the glutathione requirement observed for attenuating gap junctional communication may reflect a redox sensor activity as opposed to an antioxidant activity (190).…”
Section: Stressing Out the Neighborsmentioning
confidence: 99%